Protection of Personal Data in Business: An Overview of the Perspective of Business Ethics and Its Implications for Regulatory Compliance - Deny Susanto (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
This paper aims to provide a comprehensive analysis of the protection of personal data in the business sector from the perspective of business ethics. With the increasing use of technology and the internet, the use of personal data have become prevalent in the business world. However, the misuse of personal data has also become a significant concern for individuals and regulators alike. In this study the ethical considerations surrounding the use and disclosure of personal data by businesses. Businesses have a moral obligation to protect the personal data of their customers and stakeholders and that adherence to ethical principles is essential for long-term sustainability. This paper highlights the importance of ethical standards in the use of personal data in business